2021
DOI: 10.3389/fmars.2021.760637
|View full text |Cite
|
Sign up to set email alerts
|

Is the South-Mediterranean Canopy-Forming Ericaria giacconei (= Cystoseira hyblaea) a Loser From Ocean Warming?

Abstract: Canopy-forming brown algae support highly productive ecosystems whose decline has been attributed to the interplay of several anthropogenic disturbances. Climate change could have disruptive effects on the biology of these species, but the role of temperature in the development of early life stages is poorly understood. The aim of this study was to assess the response of Ericaria giacconei, a winter-reproducing Southern–Mediterranean endemic species, to thermal stress by testing five temperatures (12, 15, 18, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 92 publications
3
14
0
Order By: Relevance
“…Our results showed that the temperature, pH and the presence of potentially facilitating species had substantial effects on the density of recruits of Cystoseira compressa. The warmer temperature had, in agreement with our initial hypotheses, the largest negative effect on both the density and the size of recruits, as already observed on other forest-forming species, both on recruits 21,26,71 and adults 28,57,73,74 . Warmer temperatures not only affect the survival and growth of Cystoseira but also affect their metabolism 56,75,76 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results showed that the temperature, pH and the presence of potentially facilitating species had substantial effects on the density of recruits of Cystoseira compressa. The warmer temperature had, in agreement with our initial hypotheses, the largest negative effect on both the density and the size of recruits, as already observed on other forest-forming species, both on recruits 21,26,71 and adults 28,57,73,74 . Warmer temperatures not only affect the survival and growth of Cystoseira but also affect their metabolism 56,75,76 .…”
Section: Discussionsupporting
confidence: 91%
“…Seawater pH affected both the density and size of recruits in opposite ways, as density was negatively affected by the low pH, whereas size was positively affected. Low pH has been shown to negatively influence the settlement and early life stages of other key species such as the giant kelp 25,79 , corals and molluscs 38 which has led to the paradigm that early life stages could be more sensitive to global change and therefore could constitute a bottleneck 21,57 . However, in our experiment, lower pH levels positively affected the size of C. compressa, potentially showing a better performance as reported in some studies for the giant kelp 80,81 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies conducted on other representatives of the Cystoseira s.l. group such as Ericaria zosteroides (Capdevila et al, 2019), E. crinita (Verdura et al, 2021), and E. giacconei (Falace et al, 2021) reported important negative warming effects on sensitive life stages of the species.…”
Section: Final Remarksmentioning
confidence: 99%